2008
DOI: 10.1039/b718720c
|View full text |Cite
|
Sign up to set email alerts
|

Probing the effects of heterogeneity on delocalized π⋯π interaction energies

Abstract: Dimers composed of benzene (Bz), 1,3,5-triazine (Tz), cyanogen (Cy) and diacetylene (Di) are used to examine the effects of heterogeneity at the molecular level and at the cluster level on pi...pi stacking energies. The MP2 complete basis set (CBS) limits for the interaction energies (E(int)) of these model systems were determined with extrapolation techniques designed for correlation consistent basis sets. CCSD(T) calculations were used to correct for higher-order correlation effects (deltaE(CCSD)(T)(MP2)) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 64 publications
3
39
0
Order By: Relevance
“…The result indicating a possible preference of the C 6-arom ring for stacking interactions with the chelate as opposed to the other C 6-arom ring is in accordance with observations that the stacking interactions of organic heteroaromatic molecules with benzene are stronger than benzene-benzene stacking interactions (Hohenstein & Sherrill, 2009;Bates et al, 2008;Ninković et al, 2011Ninković et al, , 2012. Calculations on the stacking interactions of benzene with the pyridine molecule reveal that the presence of a heteroatom will reduce the magnitude of the dispersion, induction and exchange-repulsion components of the interactions energies.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The result indicating a possible preference of the C 6-arom ring for stacking interactions with the chelate as opposed to the other C 6-arom ring is in accordance with observations that the stacking interactions of organic heteroaromatic molecules with benzene are stronger than benzene-benzene stacking interactions (Hohenstein & Sherrill, 2009;Bates et al, 2008;Ninković et al, 2011Ninković et al, , 2012. Calculations on the stacking interactions of benzene with the pyridine molecule reveal that the presence of a heteroatom will reduce the magnitude of the dispersion, induction and exchange-repulsion components of the interactions energies.…”
Section: Resultssupporting
confidence: 91%
“…Recently the stacking interactions of aromatic and othersystems have been intensively studied (Sponer et al, 2008;Anzellotti et al, 2008;Wang et al, 2008;Bugarcic et al, 2008;Ostojić et al, 2008;Janjić et al, 2010;Hohenstein & Sherrill, 2009;Bates et al, 2008). Interactions in systems involving metal atoms and phenyl rings have received considerable attention after their description in terms of cation-interactions (Ma & Dougherty, 1997;Schmitt et al, 2003;Lovell et al, 2003;Zhu et al, 2003;Kim et al, 2003;Zarić, 1999;Zarić et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…115 By using high-level CCSD(T) studies of diacetylene and cyanide coupled with MP2 calculations performed on homo-and heterodimers of benzene and triazine, they conclude that mixed dimer systems with pi (though not aromatic) density do show unique electrostatic effects that make them more energetically favourable than indicated by previous studies of usually heterocycle-free homodimer calculations. 116,117 The Sherrill group has also relied on detailed SAPT calculations on pairs of benzene and pyridine and concluded that while dispersion is the largest stabilizing factor in parallel-offset stacks (in their work, preferred over T-shaped pairs), exchange-repulsion often cancels much of this factor, making the contribution of electrostatics relevant once more. 37 They also observe that the introduction of heteroatoms into an aromatic system shrinks its volume and makes it less polarizable; heteroatoms also make the orientation of the monomers more energetically important, as they introduce asymmetry and therefore increase the number of possible pairwise conformations to investigate.…”
Section: Theoretical Investigations Beyond Benzene and Toluenementioning
confidence: 99%
“…Neutral parallel and parallel slipped dimers have been studied computationally for closed shell cumulenes, and larger olefins. Tschumper found that neutral closed shell olefins bind with each other by stacking with very little energy, 3-5 kcal mol À1 , 38 corresponding to the Van der Waal's interaction of the two monomers. A parallel stacked ethylene dimer cation has been investigated by Pieniazek et al 39 A parallel slipped geometry was optimized and found to represent a transition state towards the open shell cation of ethylene dimer with MP2 theory.…”
Section: B Ethylene Dimer Cationmentioning
confidence: 99%